Effect of Ni/Co ratio on Ce-Sc-ZrO2 catalysts for selective H2 production via methane partial oxidation - Norah Alwadai; Ahmed S. Al-Fatesh; Kenit Acharya; Abdulaziz A.M. Abahussain; Salma A. Al-Zahrani; Anis H. Fakeeha; Naif Alarifi; Khaled M. Banabdwin; Ahmed A. Ibrahim; Rawesh Kumar (Journal of Saudi Chemical Society)
Partial oxidation of methane (POM) is a promising route for hydrogen production, and achieving a high H2 yield with an H2/CO ratio >3 is highly appealing. Optimization of Ni/Co ratios over Ce-Sc-ZrO2 (CSZ) is investigated for POM reaction and characterized by X-ray diffraction, Raman spectroscopy, temperature-programmed reduction/oxidation/desorption, and transmission electron microscopy. The active site derived from the reduction of “strongly interacted NiO” is responsible for the dissociation of C–H (of CH4), resulting high activity towards POM. 5Ni/CSZ has the highest amount of such active sites and attains the highest activity. 5Co/CSZ catalyst has cobalt-based active sites, and there is an inert carbon deposit during the reaction, causing the least activity. 3.75 wt% Ni and 1.25 wt% Co combination over CSZ support surges the highest density of basicity, oxide vacancy, and adequate amount of active sites derived from “strongly interacted NiO”. The active sites with enhanced metal-support interaction are further grown under exposure to oxidizing gas (O2) and reducing gas (H2) during the POM reaction. The highest density of basicity and oxide vacancy involves more CO2 and H2O in the sequential oxidation of CH4 under indirect pathways. The exclusive involvement of indirect pathways of POM and inhibition of hydrogen consuming reaction (like reverse water gas shift reaction) over 3.75Ni1.25Co/CSZ results into 48 % H2 yield and 3.26 H2/CO ratio up to 24 h time on stream at 600 °C. The H2 yield doubles to ∼97 %, and the H2/CO ratio comes close to 2 over 3.75Ni1.25Co/CSZ catalyst at 900 °C.